Hello avatar : rise of the networked generation - Coleman, Beth (MIT Press, 2011)
Hello Avatar! Or, llSay(0, "Hello, Avatar!"); is a tiny piece of user-friendly code that allows us to program our virtual selves. In Hello Avatar, B. Coleman examines a crucial aspect of our cultural shift from analog to digital: the continuum between online and off-, what she calls the "x-reality" that crosses between the virtual and the real. She looks at the emergence of a world that is neither virtual nor real but encompasses a multiplicity of network combinations. And she argues that it is the role of the avatar to help us express our new agency--our new power to customize our networked life. By avatar, Coleman means not just the animated figures that populate our screens but the gestalt of images, text, and multimedia that make up our online identities--in virtual worlds like Second Life and in the form of email, video chat, and other digital artifacts. Exploring such network activities as embodiment, extreme (virtual) violence, and the work in virtual reality labs, and offering sidebar interviews with designers and practitioners, she argues that what is new is real-time collaboration and copresence, the way we make connections using networked media and the cultures we have created around this. The star of this drama of expanded horizons is the networked subject--all of us who represent aspects of ourselves and our work across the mediascape.